2016
DOI: 10.3122/jabfm.2016.06.160060
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Immunochemical Test (FIT) for Colon Cancer Screening: Variable Performance with Ambient Temperature

Abstract: Introduction Fecal immunochemical tests (FITs) are widely used in colorectal cancer (CRC) screening, but hemoglobin degradation, due to exposure of the collected sample to high temperatures, could reduce test sensitivity. We examined the relation of ambient temperature exposure with FIT positivity rate and sensitivity. Methods This was a retrospective cohort study of patients 50 to 75 years in Kaiser Permanente Northern California’s CRC screening program, which began mailing FIT kits annually to screen-eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 25 publications
6
20
1
1
Order By: Relevance
“…Several patient factors have been associated with FIT positivity and false positivity. In our analysis, women with a FIT‐positive result were about 50% more likely to have no evidence of advanced neoplasia than FIT‐positive men, which is similar to previous reports . Although other studies have reported no sex differences in FP, sex‐specific hemoglobin concentration cutoffs have been suggested.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several patient factors have been associated with FIT positivity and false positivity. In our analysis, women with a FIT‐positive result were about 50% more likely to have no evidence of advanced neoplasia than FIT‐positive men, which is similar to previous reports . Although other studies have reported no sex differences in FP, sex‐specific hemoglobin concentration cutoffs have been suggested.…”
Section: Discussionsupporting
confidence: 89%
“…In our analysis, women with a FIT-positive result were about 50% more likely to have no evidence of advanced neoplasia than FIT-positive men, which is similar to previous reports. 39,40 Although other studies have reported no sex differences in FP, 21,23 sex-specific hemoglobin concentration cutoffs have been suggested. In a large study that evaluated PPV for advanced neoplasia at varying hemoglobin concentration cutoffs, the PPVs achieved for women (33%-43%) were lower than for men (53%-63%) at every hemoglobin cutoff.…”
Section: Discussionmentioning
confidence: 92%
“… 13 Thus, some decrease in sensitivity and an increase in specificity of FIT when returned at high temperatures were expected. Several previous population-based studies investigated the association between ambient temperatures and positivity, but not sensitivity and specificity of FIT, 6 , 9 12 , 14 and most of them found a negative association between higher temperatures and FIT positivity. The largest study, 6 with nearly 200,000 evaluated FITs conducted in Florence, Italy, indicated that a 1°C increase in temperature decreased FIT positivity by 0.7% and that detection rates for AN were by 13% lower in summer than in winter.…”
Section: Discussionmentioning
confidence: 95%
“…Only at even higher temperature ranges (26.1–35.0°C and >35°C), positivity decreased strongly, by 22% and 41%, respectively. A study from California 12 (N=472,542) found differences in FIT positivity by month, with higher positivity rates during the winter months. Absolute differences in sensitivity of detecting CRC (estimated by record linkage with cancer registry data rather than by comparison with colonoscopy results) were small, however, ranging from 75% in June/July to 79% in December/January.…”
Section: Discussionmentioning
confidence: 99%
“…By looking at over 1.1 million mailed Fecal Immunochemical Tests, Doubeni et al 5 found that the sensitivity of the test varies with seasonal temperature changes. The authors discuss some interesting implications of this discovery as it applies to the planning and execution of population-based colorectal cancer screening programs.…”
mentioning
confidence: 99%